A new species of Phrixotrichus (Araneae, Theraphosidae) from southwestern Argentina and new distributional data for P. vulpinus - Ferretti, Nelson Edgardo (2015)
A new species of Phrixotrichus Simon, 1889, P. pucara sp. nov., is described and illustrated based on a male from Pucará river, Neuquén province, Argentina. Male can be distinguished from all other species of the genus by the presence of a long strong spine on inner face of prolateral branch of tibial apophysis; also, it differs from P. scrofa (Molina, 1788) and P. vulpinus (Karsch, 1880) by a serrated prolateral keel of the male palpal bulb. Male resembles P. jara Perafán & Pérez-Miles, 2014 but can be distinguished by the uniform color on dorsal cephalothorax and by the palpal organ morphology being wider on the bulb base and embolus shorter and thicker, with the tip of embolus not so directed retrolaterally and prolateral keel bearing a serrated edge with three teeth. Additionally, P. vulpinus is reported for the first time for Argentina along with new distributional data.